Intersecting the Academy: Legitimizing Applied & Professional Studies at the Post-Graduate Level - Laura Servage (Adult Education Research Conference, 2006)
Given an increasing demand for continuing professional education at the graduate level, what is the appropriate role of the university? Applied graduate degree programs, in the interests of CPE for working adult students, may be perceived as a threat to the hegemony of the traditional academy, or as a new opportunity for the university to “serve.”
Keywords: continuing professional education; graduate studies